Colloidal properties of polymer amended Cyprus bentonite for water-based drilling fluid applications - Ramsis, Youstina; Gravanis, Elias; Sarris, Ernestos (My University, 2024)
In this work, we investigate the capability of a waste bentonite from the Polycanthos quarry in Cyprus, as a low-density solid additive to create colloids that are used in water-based drilling fluid systems (WBF) in drilling operations. Repurposing waste bentonite aligns with environmental sustainability and when properly processed can serve as a cost-effective solution to achieve the desired colloidal properties for WBF. Samples were obtained from waste stockpiles and were mechanically processed to a size < 63 µm. The material was activated with soda ash via three different methods investigating optimum soda ash percentage and curing time. Standard tests were performed for the rheological behavior and filtration properties and the results indicated that the quality of the activated clay dispersions improved slightly but the desired colloidal properties were not obtained. This can be attributed to the K+-rich clay and non-clay impurities that are inherent in the material so further amendment with xanthan gum polymer was conducted, at various concentrations. Results of this work show that with minor polymer addition, the material under investigation reaches the desired colloidal properties and qualifies according to API standards for WBF. Exploiting local waste clay material in WBF application leads to the development and sustainability of local resources thus contributing to the circular economy principle.
Keywords: Soda-ash activation methods; Drilling fluid systems; K+-bentonite; Xanthan gum polymer amendment; Circular economy; Sustainable development